MODERN METHODOLOGICAL TOOLS FOR STUDENTS' LANGUAGE SKILLS SELF-ASSESSMENT - A. N. Astanina; N. O. Verbitskaya (Russian State Vocational Pedagogical University, 2017)
Introduction. Nowadays, the problem of standardization of foreign language training at the higher school is becoming currently topical. With regard to the processes of globalization, the international educational projects and students exchange programs gain greater international recognition. Such international programmes involve foreign language knowledge graded as not only high certified academic levels but also as basic language skills. The lack of foreign language competence becomes the obstacle for successful training, depriving a future graduate of a part of chances to become the competitive and popular expert in the chosen profession. The success of a foreign language course completion among students depends on many factors; the most important factor is motivation which can affect self-assessment of training results. The aim of the study is to describe possibilities of the CanDos tools implementation for the organization of students self-consciousness and self-assessment of own achievements in order to influence the motivation for mastering a foreign language.Methodology and research methods. The research is based on competencybased approach. The methods involve comparative analysis, synthesis, and generalization.Results and scientific novelty. The questionnaire developed for the experiment helped to collect the data concerning the effectiveness of the CanDos software implementation for self-assessment of students' foreign language skills. The corresponding self-assessment helps students to carry out a self-reflection of own knowledge and abilities, and to find "weak points" in language proficiency which need additional practice and improvement. By regularly using CanDos software as self-assessment tools, students learn to identify the correspondence of their language competence to the external requirements and standards of education. Orientation to training results will help future experts to create self-motivation that positively affects indicators of progress and internal satisfaction of each student.Practical significance. The data received can be applied by teachers of foreign language departments of non-linguistic higher education institutions; teachers and psychologists who are engaged in studying of aspects of training motivation.